2021
DOI: 10.14203/stipm.2021.308
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Open Innovation in SMEs: Implementation, Success Factors and Challenges

Abstract: <p><strong><em>Abstract</em></strong></p><p><em>This literature review explores the Open Innovation of SME companies, their application, success factors, impact, and challenges. The theoretical framework is built starting from the definition, a critical pillar, and Open Innovation in SME companies. The main factor in the Open Innovation process stage is finding innovative ideas and establishing network access with the external environment. Balanced, systematic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Referring to the literature review method by Wibisono (2021), I started this research by conducting a simple bibliometric analysis using the main database, Web of Science, then performing a research network analysis using the VOS Viewer software. I apply the keywords "innovation; polic*; qualitative; quantitative; mix*; method*" to collect article data and exclude other kinds of documents.…”
Section: Methodsmentioning
confidence: 99%
“…Referring to the literature review method by Wibisono (2021), I started this research by conducting a simple bibliometric analysis using the main database, Web of Science, then performing a research network analysis using the VOS Viewer software. I apply the keywords "innovation; polic*; qualitative; quantitative; mix*; method*" to collect article data and exclude other kinds of documents.…”
Section: Methodsmentioning
confidence: 99%
“…The study found two contingency factors that mediate the relationship between the variables under study such as external country or regional institutions and internal characteristics of the firm such as human capital, size, and experienced professionals. Wibisono (2021) opined that it is challenging to compare the empirical findings of individual OI literature since the outcomes are fragmented. The implementation of OI in SMEs is not only complex, but also may bring several risks such as financial and managerial constraints and information access.…”
Section: Open Innovationmentioning
confidence: 99%
“…Collaboration between firms is necessary to achieve success regarding innovation. (Wibisono, 2021). Yao, Wang, Yu and Guchait (2019) found that open innovation is positively influenced by external knowledge.…”
Section: Theoretical Reviewmentioning
confidence: 99%